Histopathological Features of Aneurysmal Bone Cyst of the Temporal Bone – A Case Report and Review of Literature - Liu, Shiquan; Jassim, Ali; Bleeker, Jonathan; Chen, Frank; Kolanuvada, Bangaruraj; Rong, Rong; Liu, Weiguo (North American Journal of Medicine and Science, 2015)
Aneurysmal bone cyst (ABC) is a rare lesion. We described an ABC of the temporal bone. The patient was a 46-year-old woman presenting with a progressively enlarging mass in the left temporal region with unknown duration. A CT revealed a 3 x 3.5 cm osteolytic lesion involving the left temporal bone. MRI revealed a 3.6 x 2.6 x 2.7 cm well-defined expansile lesion centered in the left temporal bone. The patient subsequently underwent MRI-guided stereotactic left frontotemporoparietal craniectomy and the lesion was completely removed. Following surgery, the patient has been followed for the past 9 months without evidence of residual/recurrent disease. Morphologically, the lesion consisted of cystic and solid areas. The cystic areas demonstrate multi-cystic architecture between bony trabeculae separated by thick septa. These septa contained abundant fibroblasts, spindle-shaped stromal cells, and giant cells with scattered hemosiderin laden macrophages. The solid areas consisted of spindle-shaped stromal cells with oval nuclei, proliferating blood vessels, mononuclear cells and some interspersed multinucleated giant cells.